Análisis Financiero a la Empresa Kradac Cía. Ltda. en la ciudad de Loja, periodo 2021-2022 - Jiménez Cordero, Erika Mariana (2024)
Currently, the evaluation of a company's economic and financial situation, as well as its performance, involves the review and assessment of financial statements that provide essential information for strategic decision-making within the organization. This research study aims to conduct a financial analysis of Kradac Cía. Ltda., located in the city of Loja, for the period 2021-2022. The study employs a mixed-methods approach of a cross-sectional nature, utilizing various methods such as deductive, inductive, and mathematical techniques to achieve the research objectives. Through the application of vertical and horizontal analysis, the economic and financial structure of the company was determined alongside the variations that have occurred. The analysis revealed total assets amounting to $729,034.98 for the year 2021 and $719,242.74 for 2022. Additionally, the horizontal analysis indicated a 67% increase in profits for the year 2022 compared to 2021, attributed to an increase in sales and a decrease in administrative costs and expenses in 2022. Finally, the financial indicators of activity, liquidity, indebtedness, and profitability, as established by the Superintendency of Companies, Securities and Insurance, were applied. The indicators of activity and indebtedness did not meet the established standards, reflecting an increase in the indebtedness and leverage ratios. In conclusion, the company experienced a 67% increase in profits, a reduction in accounts payable to third parties, and an increase of $1.18 in the company's current liquidity.